Evaluation of the Organoleptic Attributes and Acceptability of Cotton Fabric Treated with Dyes Extracted from Beetroot (Betavulgaris) Indigenous Plant for Fabric Coloration - S.U, Ozougwu; E. U., Anyakoha (Journal of Home Economics Research, 2024)
This study evaluated the organoleptic attributes and acceptability of cotton fabric treated with dyes extracted from beetroot [Beta vulgaris] indigenous plant for fabric coloration. The study design was Research and Development (R and D) and was conducted at the University of Nigeria, Nsukka. The study population comprised 41 evaluators made up of 17 Lecturers and 24 Postgraduate students from University of Nigeria, Nsukka. Organoleptic Attributes and Acceptability Evaluation [OAAE] instrument was used for data collection and data were analyzed using descriptive statistics. t-test statistic tested a null hypothesis at 0.05 Level ofsignificance There were no significant differences(P>0.05) in the mean rating responses of lecturers and postgraduate students on the acceptance of the organoleptic attributes of the beetroot dye on cotton fabric in six instances but difference existed in one instance. The null hypothesis was therefore accepted in six instances and rejected in one instance at 0.05 probability level. Recommendations were made based on the findings.